PENENTUAN KARAKTERESTIK PRESTASI TERBANG PESAWAT UDARA BERMESIN TURBOPROP DARE DATA UJI TERBANG MANUVER TAK STASIONER (STUDI KASUS PESAWAT UDARA N250-PA1) - Dian Widorini , Nungki
Determination of aircraft performance characteristics from flight test data is usually carried out from stationary flight test maneuver. This stationary maneuver is hardly performed by test pilots. Also, this maneuver is very time consuming, so that the operational cost of the flight test program becomes more expensive. The approach pursued in this thesis towards the determination of aircraft performance characteristics from non-stationary flight test maneuver compared to the stationary maneuver, this non-stationary maneuver is relatively easy to carry out and not time consuming. Parameter identification technique is used in the analysis of flight test data obtained from non stationary flight test maneuvers. This technique is used to estimate the aerodynamic parameters of the aircraft. Next, the performance characteristics of the aircraft is derived from the estimated aerodynamic parameters. Results of a flight test program to determine the aircraft performance characteristics with the N-250 PAI prototype aircraft of PT IPTN are presented in this thesis. Comparison with other flight test results using flight test data obtained from stationary maneuvers is also given.